2019
DOI: 10.1016/j.jtho.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of LKB1 Activity on the Sensitivity to PI3K/mTOR Inhibition in Non–Small Cell Lung Cancer

Abstract: Introduction: Liver kinase B1 (LKB1), also called serine/ threonine kinase 11 (STK11), is a tumor suppressor that functions as master regulator of cell growth, metabolism, survival, and polarity. Approximately 30% to 35% of patients with NSCLC possess inactivated liver kinase B1 gene (LKB1), and these patients respond poorly to antiprogrammed cell death 1 (PD-1)/programmed death ligand 1 (PD-L1) immunotherapy. Therefore, novel therapies targeting NSCLC with LKB1 loss are needed. Methods: We used a new in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…A recently published paper shows that the dual inhibition of mTOR and PI3K can be a promising therapeutic strategy for LKB1-deficient tumors. 30 These data are in line with our results where we inhibited the PI3K and mTOR target S6 through the inhibition of ERK/p90RSK/S6 axis.…”
Section: Discussionsupporting
confidence: 91%
“…A recently published paper shows that the dual inhibition of mTOR and PI3K can be a promising therapeutic strategy for LKB1-deficient tumors. 30 These data are in line with our results where we inhibited the PI3K and mTOR target S6 through the inhibition of ERK/p90RSK/S6 axis.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, ~30% of patients with NSCLC are reported to have mutations in LKB1 worldwide (52). LKB1 mutations can cause abnormal phosphorylation of the PI3K/mTOR pathway, and participate in the progression of lung cancer (53). Han et al (54) revealed that LKB1 inhibited the proliferation of periosteal mesenchymal progenitors and xenograft tumors by inhibiting mTOR phosphorylation, and demonstrated that the LKB1-mTORC1 pathway may be a target for treating osteogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It forms two distinct complexes, called mTOR complex 1 (mTORC1) and mTORC2, of which only mTORC1 is sensitive to the macrolide rapamycin [30][31][32]. Specifically, mTORC1 can phosphorylate ribosomal protein S6 kinase (S6K) and eIF4E binding protein 1 (4EBP1) to increase translation of mRNAs, while mTORC2 controls cell survival via activation AKT and SGK1 pathway [33,34]. Initial studies mainly focus on inhibition of mTORC1 with rapamycin.…”
Section: Discussionmentioning
confidence: 99%